Enhancing students’ learning creativities through the application of literacy learning model in the Merdeka Belajar Kampus Merdeka (MBKM) curriculum program - Holmes Rajagukguk; Juandi Nababan; Lamhot Situmeang (UNIB Press, 2022)
The purpose of this study is to investigate the improvement of elementary students’ learning creativities during online learning through the application of the literacy learning model. Therefore, classroom action research (CAR) was applied in this study and practice, this study implemented two cycles in which one (1) cycle consisted of planning, action, observation and reflection. A test which consists of observing, asking, reasoning, trying and communicating elements was used to collect the data. As a result, this study indicates that there was a significant improvement in test results which only 47% of students passing in cycle one (1) and an increase to 94% in cycle two (2). Thus, the use of the literacy learning model is very much recommended to be implemented to enhance students' learning creativities during online learning.